Progressive Islamic Education Integrates Science in the Islamic Insight Perspective of Muhammadiyah - Lety Febriana; Akhsanul In'am; Khozin Khozin; Rifa'i Rifa'i (UIN Fatmawati Sukarno Bengkulu, 2025)
The purpose of this research is to reveal the relationship of progressive Islam in the context of developing Muhammadiyah education science. Describing the dynamics of Muhammadiyah educational institutions with the understanding of the Islamic doctrine of its managers and identifying scientific values as an effort to understand and develop progressive education. The renewal of Islamic thought (tajdid) that is able to push towards the progress of social life is a reformist and progressive religious renewal. The concept of science in the ideology of progressive Islam refers to the phenomenon of Muhammadiyah, which consistently believes that Islam contains the integration of modern science and Islamic teachings in order to realise the life of people who are spiritually strong and advanced in social life. Scientific values such as creativity and innovation as well as collaboration and communication are needed to realise progress in the world of education. Muhammadiyah education requires applicative steps that include sharpening or renewing applications as an educational process that develops the potential for excellence. The progress that Muhammadiyah aspires to is an effort to realise people who excel in various aspects, both spiritual and outward aspects. The method used in data collection in this study is the documentation method by recording and analysing relevant available reports. The data analysis technique used is content analysis in order to obtain conclusions from the analysed documents. The result of this paper is Islam berkemajuan as an ideology in Muhammadiyah education, which integrates science with Islam in life so as to form a systematic comprehensive blend between faith and modernisation of social institutions. The concept of advanced Islamic education, which is Muhammadiyah's worldview, is in accordance with the value of science that contains creativity and innovation and is able to collaborate in reflecting the values of humanisation, liberation and transcendence.